A comparative analysis of dynamic and cross-sectional approaches for financial performance analysis. (2018) - Alimohammadlou, Moslem; Bonyani, Abbas
The use of financial ratios as the necessary information is considered as one of the noticeable issues for researchers to apply quantitative models for evaluating the performance of institutions. The reason for introducing these new approaches is that the financial ratios cannot individually provide a correct and adequate understanding of an institution's performance. This study is aimed to compare the cross-sectional analysis and dynamic analysis to evaluate the financial performance. In this regard, 14 companies were examined based on two approaches during the period of 2011-2015 using the five influential ratios on financial performance evaluation. Then, results were compared to data of the test period (2016). Results showed that applying the dynamic analysis of performance instead of cross-sectional analysis and also carefully consideration in the analysis of efficient frontier shift can provide a more accurate evaluation of financial performance of companies compared to the multi-criteria decision-making analysis.